Pemanfaatan Getah Pinus dan Perannya Terhadap Penghidupan Masyarakat di Provinsi Sulawesi Selatan - Tajuddin Tajuddin (ULIN: Jurnal Hutan Tropis, 2021)
Pine forest in South Sulawesi is one of the evidence of successful reforestation and has been utilized by the community in the form of tapping pine resin. This article explains the permits types of the utilization/collection of pine resin by the community, the role of pine resin in community livelihoods, and various problems in the utilization of pine resin by the community in South Sulawesi. Qualitative/quantitative descriptive analysis is used to analyze primary data obtained through interviews and secondary data analysis obtained from relevant agencies. We found that the utilization/collection of pine resin in South Sulawesi by the community used four schemes or permits types, namely: Business License for Non-Timber Forest Product Utilization, Licence for Collection of Non-Timber Forest Products, Social Forestry Schemes Permits, and Cooperation of Forest Utilization. Furthermore, for the community livelihoods, utilization/collection of pine resin has provided extra incomes and employment for local communities and workers from outside. However, labor limitations, fluctuations in the price of pine resin, relying on the community on business partners, and tapping techniques that contradict the principle of forest sustainability is still becoming the problems in the utilization/collection of pine resin in South Sulawesi.